Peran Pendidikan Jasmani untuk Mewujudkan Tujuan Pendidikan Nasional - Pinton Setya Mustafa (Peneliti.net, 2022)
A regulation in Indonesia the national goal of education is to develop the ability and form the character and civilization of a dignified nation in order to educate the nation's life. The purpose of this article is to examine the role of physical education in realizing national education. The method in this research uses a qualitative approach to the type of literature study. This study seeks to explore document studies on the study of physical education in general and then relate it to the goals of national education. In the theoretical study the elements of physical education play a role in realizing the national goals of education. Because physical education programs and objectives essentially shape human character to be good through the medium of motion. Learners can grow and develop well physically, psychomotor, cognitive, and in attitude as a result of the contribution of physical education programs in schools. So physical education should not be ignored within the scope of the education unit, and physical education needs to be considered in its implementation in order to achieve the expected goals. The conclusion obtained is that the role of physical education is very important to form healthy human beings, have a noble mind, and have a good mindset, so that they can contribute to realizing the goals of national education that form superior human resources in the future.